PhysiCombat: A Projectile Motion Multiplayer Turn-Based Physics Game on Android - Joe Yuan Mambu (CogITo Smart Journal, 2020)
School lessons can be uninteresting and even dull. Subjects like maths, physics or chemistry are on top of the list, and one topic that often hard to grasp is the projectile motion lesson. Gamification is seen as one of the concepts where learning can be much more engaging. Using Unity 3D, we were able to develop gamification of the projectile motion lesson. By transforming it into an Angry Birds look alike, the learning process is experienced in this turn-based game become much more enjoyable. Instead of pointing where to shoot, students are asked to calculate the velocity by taking the given value such as angle and distance. The game can be played alone, as in practice mode, or two players as in versus mode or even two groups which is very applicable in a class (i.e. Group 1 vs Group 2) and since it uses real physics equation, the application able to show a realistic simulation of the projectile motion path. School lessons can be uninteresting and even dull. Subjects like maths, physics or chemistry are on top of the list, and one topic that often hard to grasp is the projectile motion lesson. Gamification is seen as one of the concepts where learning can be much more engaging. Using Unity 3D, we were able to develop gamification of the projectile motion lesson. By transforming it into an Angry Birds look alike, the learning process is experienced in this turn-based game become much more enjoyable. Instead of pointing where to shoot, students are asked to calculate the velocity by taking the given value such as angle and distance. The game can be played alone, as in practice mode, or two players as in versus mode or even two groups which is very applicable in a class (i.e. Group 1 vs Group 2) and since it uses real physics equation, the application able to show a realistic simulation of the projectile motion path.